Studying the Tensile and Buckling for PMMA Reinforced by Jute Fibers for Prosthetic Pylon - Jawad Kadhim Oleiwi; Shaymaa Jumaah Ahmed (Engineering and Technology Journal, 2016)
The main objective of this research is studying the tensile and buckling of Jute fibers reinforced composite by varying the number of Jute fibers layers and fibers angle (±45°&0°/90°). Vacuum bagging technique was adopted for the preparation of laminated composite specimens that made from PMMA as matrix and Perlon layers with different number of Jute fibers layers as reinforcement materials. Also the finite element method (ANSYS-15) was used by creating a model of prosthetic pylon and applied compressive load at heel strike step from gait cycle to know the critical buckling stress. The results showed that the best laminated composite specimens have three Jute fibers layers at (0 º /90 º) fibers orientation relative to applied load. Where, the critical buckling stress, tensile strength, and modulus of elasticity were (442MPa, 61MPa, and 3.75GPa) respectively, while, the percentage elongation was (2.1).